Heat transfer in Ar and N₂ doped solid CO - Romanova, T.V.; Stachowiak, P.; Jeżowski, A. (Физика низких температур, 2015)
The measurements of thermal conductivity coefficient of a solid carbon monoxide crystal containing argon
and nitrogen admixtures at different concentrations (1.5, 3, 6, 12.5, 25% for N2 and 0.5, 1, 1.25, 2, 4% for Ar)
were performed in the temperature range from 1.5 to 40 K by steady-state heat flow method. For analysis of the
experimental data the Callaway method in the framework of the Debye model was used. The contribution of various
mechanisms of phonon scattering, including scattering by disordered dipoles of the CO matrix, to the thermal
conductivity of CO–N₂ and CO–Ar solid solutions were taken into account.